Public order policing: a professional's guide to international theories, case studies, and best practices - Bürger, Bernd; Madensen, Tamara; Lee, Ryan (Springer, 2024)
Successful public order management is critical to upholding democracy and maintaining the rule of law. Negative police-public interactions during assemblies can impact the safety and well-being of citizens and officers, as well as local and international perceptions of police legitimacy. As observed during events across the world, including assemblies in the U.S., Myanmar, Belarus, Russia, and elsewhere, police mismanagement of mass demonstrations often instigates crowd violence and other harmful behaviors. The causes of violence at assemblies are complex and multi-faceted. Failure to understand crowd dynamics that lead to violence limits police effectiveness and contributes to poor officer decision-making. This book offers an international review of public order management experiences and effective practices. Practical examples, grounded in multi-disciplinary theory and science, offer a roadmap to improve police response and increase safety at assemblies in democratic countries. The diverse content, perspectives, and lessons learned presented in this volume will serve as a useful guide for all people working in the field of public order management, including police officials, policymakers, and researchers. This edited volume was written by and for practitioners, pracademics, and academics to review the complex and demanding task of policing public order